Validation of an educational tool on healthy eating for schoolchildren - Ribeiro de VASCONCELOS, Celia Maria; Ribeiro de VASCONCELOS, Eliane Maria; Lucena de VASCONCELOS, Maria Gorete; Brito de AZEVEDO, Suelen; Falcão RAPOSO, Maria Cristina; Ribeiro de VASCONCELOS, Ana Lucia (Revista de Nutrição, 2023)
Objective The purpose of this study was to validate the card game The Enigma of the Pyramid about healthy eating, using judges (expert) for the validation of content and design; and the target population (students from the 4th and 5th grades, aged 9-10 years) for the semantic validation (pilot test). Methods The Item-Level Content Validity Index was used to verify the degree of agreement among the experts’ opinions, item by item; and the Scale Level Content Validity Index to determine the arithmetic mean of the proportion of items that receive judgments of “non-disagreement” by the judges. The item that obtained Item-Level Content Validity Index greater or equal to 0.80 and Scale Level Content Validity Index greater or equal to 0.90 was considered validated, which was the coeffi cient of validity. The binominal test was used to select the items that should be revised/modifi ed, using the p-value of ratio (reject H0 if p≤0.8). Items were validated at signifi cance level of ≤0.05. Results Twenty-two judges and 12 schoolchildren participated in the study. Of the 23 items of the card game, nine were selected for review/modification, of which five were from the language component and four from the suitability component for the target population. Conclusion Once the modifications were made, they were all approved by all participating students, making this educational tool on healthy eating habits available for use with the student population.